The fabrication of iron oxide nanoparticle‐nanofiber composites by electrospinning and their applications in tissue engineering. Issue 7 (21st June 2017) - Mortimer, Chris J.; Wright, Chris J.
Abstract: This paper reviews the use of iron oxide nanoparticle‐nanofiber composites in tissue engineering with a focus on the electrospinning technique. Electrospinning is an established method of scaffold fabrication offering a number of key advantages which include its facile nature, with electrospun materials offering a high surface area to volume ratio, potential for the release of drugs and antimicrobials, controllable fiber diameters and high porosity and permeability. A number of different techniques for the preparation of iron oxide nanoparticles including their functionalization are discussed along with their applications in the biomedical field. The review then focusses on the fabrication of nanoparticle‐nanofiber composite scaffolds formed using electrospinning. The advantages and disadvantages of current fabrication techniques are discussed including the fabrication of nanofibers using pre‐synthesized nanoparticles and post‐treatment synthesized nanoparticles. We demonstrate that emerging in‐situ synthesis techniques show promise by offering a reduced number of steps and simpler procedures for the production of magnetic scaffolds. These scaffolds have a number of applications in tissue engineering, allowing for improved bone and tissue repair. Abstract : Iron oxide nanoparticle‐nanofibre composites can be used to improve the functionality of scaffolding material which is used to support cell growth within tissue engineering. Electrospinning is an established method for the creation of polymer scaffolds from nanofibres it offers many advantages which include a high surface area to volume ratio, potential for the release of drugs and antimicrobials, controllable fibre diameters and high porosity and permeability. Modern techniques have emerged that allow scale up for economic manufacture of scaffolds for tissue engineering. This review focusses on the fabrication of nanoparticle‐nanofibre composite scaffolds formed using electrospinning and argues that emerging in‐situ synthesis techniques show promise by offering a reduced number of steps and simpler procedures for the production of magnetic scaffolds.